Assessment of stress and its risk factors among primary school teachers in the Klang Valley, Malaysia - Abdul Samad, Nurul Izzah; Hashim, Zailina; Moin, Saidi; Abdullah, Haslinda (Canadian Center of Science and Education, 2010)
Introduction: This cross-sectional study determined the workplace stressors, stress levels, mental health status and their influencing factors, among primary school teachers in the Klang Valley, Malaysia.